A fuzzy cognitive mapping model for service supply chains performance. Issue 4 (20th November 2017) - Rezaei Pandari, Abbas; Azar, Adel
Abstract : Purpose: The aim of this study is to present a model for service supply chain performance evaluation (SSCPE) based on fuzzy cognitive mapping (FCM). Design/methodology/approach: Despite the unique nature of services, which distinguishes them from goods, the performance evaluation of service supply chains (SSCs) has still not received adequate attention from researchers or practitioners. With the help of in-depth interviews conducted with insurance industry experts in Iran, the performance measures of SSCs are defined, and the relevance between the performance measures, which are based upon the knowledge of experts in this field, are presented as a fuzzy cognitive map. Findings: By blocking the aggregate map of experts, a model for SSCPE is developed that discusses performance measures and metrics of strategic, tactical and operational SSC processes, such as service-providing management, service-enabling management, market management, cash-flow management, customer-relationship management, supplier-relationship management, knowledge- and information-flow management and risk management. Indexes of FCM models indicate that the supply chain service quality and strategy blocks have the most importance compared with others. Originality/value: The paper develops an original SSCPE model that can be used as a basis for SSC improvement and develops an excellence model for SSC.